Elucidating the molecular interaction of serum albumin with nizatidine and the role of β-cyclodextrin: multi-spectroscopic and computational approach. Issue 5 (23rd March 2020) - Rahman, Yusra; Afrin, Shumaila; Alhaji Isa, Mustafa; Ahmed, Shahbaz; Tabish, Mohammad
Abstract: Nizatidine is a histamine H2 receptor antagonist which act by inhibiting the production of stomach acid, thereby, finds its application in treating various diseases related to the gastrointestinal tract. Studying albumin–drug interaction is important for understanding the pharmacokinetics and pharmacodynamics of therapeutic candidates. In the present work, the interaction of nizatidine with BSA was investigated by employing multi-spectroscopic and computational studies. The formation of BSA–nizatidine complex was characterised by UV-visible and fluorescence based-spectroscopic studies. Steady-state fluorescence demonstrated the static mode of quenching of BSA by nizatidine. The interaction was spontaneous and nizatidine binds to BSA with a stoichiometry of 1:1. Forster resonance energy transfer calculations revealed that there was a high possibility of energy transfer between nizatidine and BSA. The resultant secondary structural change in BSA on the addition of nizatidine was studied by circular dichroism spectroscopy. Moreover, synchronous and three-dimensional fluorescence spectroscopy was used to determine the conformational changes occurred in the structure of albumin on the binding of nizatidine. Competitive-site marker experiments suggested that nizatidine binds in the Sudlow site II of BSA. Additionally, the effect of β-cyclodextrin as an inclusion compound on the interaction was studied. Furthermore, molecular modelling and simulation studies were performed to corroborate the results obtained above. Communicated by Ramaswamy H. Sarma